Organ Trade in Nigeria: A Governance Challenge amidst Socioeconomic Pressures - Adeyanju, Faith O. Adeyanju; Nwogwugwu, Ngozi Nwogwugwu; Adewumi, Eyitayo F. Adewumi (African Journal of Stability and Development (AJSD), 2025)
Organ transplantation is an advanced medical procedure which offers hope to patients with failing organs. However, the number of persons who require an organ far exceeds the number of organs available through voluntary donations. This imbalance has bred illegal organ trade, an unlawful activity of buying and selling of human organs. This study adopted structural functionalism as the theoretical perspective, which maintains that political structures have their functions, such as rule making, application and adjudication to ensure equilibrium in the system. Using an exploratory research design, interviews were conducted with four organisations and three medical professionals, and the data were analysed using narrative analysis. The research found that economic desperation, weak legislation and lack of political will contribute significantly to the thriving illegal markets in Nigeria. Therefore, the research recommended the implementation of economic programmes to reduce the susceptibility of vulnerable persons to exploitation by traffickers. Also, there is an urgent need to amend the National Health Act 2014 to include comprehensive provisions addressing organ donation and transplant processes in Nigeria.